Expansion-repression mechanism for scaling the dpp activation gradient in Drosophila wing imaginal discs. - Ben-Zvi, D.; Pyrowolakis, G.; Barkai, N.; Shilo, B.Z. (Current Biology, 2011)
Maintaining a proportionate body plan requires the adjustment or scaling of organ pattern with organ size. Scaling is a general property of developmental systems, yet little is known about its underlying molecular mechanisms. Using theoretical modeling, we examine how the Dpp activation gradient in the Drosophila wing imaginal disc scales with disc size. We predict that scaling is achieved through an expansion-repression mechanism [1] whose mediator is the widely diffusible protein Pentagone (Pent). Central to this mechanism is the repression of pent expression by Dpp signaling, which provides an effective size measurement, and the Pent-dependent expansion of the Dpp gradient, which adjusts the gradient with tissue size. We validate this mechanism experimentally by demonstrating that scaling requires Pent and further, that scaling is abolished when pent is ubiquitously expressed. The expansion-repression circuit can be readily implemented by a variety of molecular interactions, suggesting its general utilization for scaling morphogen gradients during development.